Restless leg syndrome, periodic limb movements, febrile seizures and Attention deficit hyperactivity disorder in an Indian family - Meena Gupta; Amit Batra; Anurag Trivedi; Debashish Chowdhury; Geeta A Khwaja (Annals of Indian Academy of Neurology, 2012)
Restless leg syndrome (RLS) is a common neurological disorder which can affect individuals of all age groups and incidence increasing with age. It can cause severe sleep disruption and negatively impact quality of life of an individual. Its diagnosis is clinical, based on essential criteria of International RLS Study Group. It can be idiopathic or associated with various medical and other neurological disorders. Idiopathic RLS can be sporadic or may have a familial inheritance, with several genetic loci been reported till date. RLS has a strong association with periodic limb movements, both sleep and awake. Very few studies of familial RLS/Periodic limb movements in sleep and their associations have been reported. We report an Indian family with autosomal dominant RLS/PLMS, with RLS and PLMS as well as psychiatric disorders, febrile seizures and Attention Deficit Hyperactivity Disorder in different family members, over three generations.